Enterococcus faecalis Is a Better Competitor Than Other Lactic Acid Bacteria in the Initial Colonization of Colon of Healthy Newborn Babies at First Week of Their Life - Al-Balawi, Mohammad; Morsy, Fatthy Mohamed (Frontiers in Microbiology, 2020)
Initial colonization of human gut by bacteria is an important step in controlling its microbiota and health status. This study followed the initial colonization by lactic acid bacteria (LAB) in colon of new born babies through following its occurrence in their stool at first week of their life. The LAB occurrence in the neonates' stool was followed on MRS agar medium. The isolated LAB from male and female newborn babies of normal birth and cesarean section surgical delivery were molecular biologically identified by phylogenetic analysis of 16S rRNA gene sequence. From the 24 investigated newborn babies, three LAB taxa, Lactobacillaceae, Enterococcus and Streptococcus, were detected in their stool at first week of their life. Lactobacillaceae represented 20.8% of total colonized LAB in newborn babies in the culture-dependent approach used in this study and included three species namely Limosilactobacillus reuteri (previously known as Lactobacillus reuteri), Lacticaseibacillus rhamnosus (previously known as Lactobacillus rhamnosus) and Ligilactobacillus agilis (previously known as Lactobacillus agilis). Enterococcus faecalis and E. faecium were detected where E. faecalis was the highest dominant, representing 62.5% of total LAB colonizing newborn babies. This result suggests that this bacterium has high potency for colonization and might be important for controlling the initial settlement of microbiota in healthy newborn babies. Only one species of Streptococcus namely Streptococcus agalactiae was detected in 8.33% total of the investigated newborn babies indicating high competency by other LAB for colonization and that this bacteria, in spite of its pathogenicity, is commensal in its low existence in healthy babies. The explored potency of natural initial colonization of the LAB species E. faecalis, E. faecium, L. reuteri, L. rhamnosus and L. agilis of which many health beneficial strains were previously reported, would be important for future applications. Despite the controversy in evaluating its health benefits, E. faecalis as a potent competitor to other LAB refers to its importance in initial colonization of healthy babies colon at first week of their life. Further future studies, with more number of samples and characterization, would be of importance for evaluating the potential use of beneficial Enterococcus strains which could improve intestinal ecosystem.